Advances in cardiac imaging: the role of magnetic resonance imaging and computed tomography in identifying athletes at risk - Prakken, N. H.; Velthuis, B. K.; Cramer, M. J.; Mosterd, A. (British Journal of Sports Medicine, 2009)
Advanced cardiac imaging, using cardiac magnetic resonance imaging (MRI) and multidetector computed tomography (CT), is increasingly used in the work-up of athletes with suspected abnormalities on screening. Both imaging modalities produce highly accurate and reproducible structural and functional cardiac information. Cardiac MRI has the advantage of imaging without radiation exposure or the use of iodine-containing contrast agents, but is sometimes not possible due to claustrophobia or other contraindications. Although cardiac MRI can rule out coronary artery anomalies, multidetector CT is superior to cardiac MRI for visualising the full extent of the coronary arteries and atherosclerotic coronary artery disease. For patients less than 35 years of age, cardiac MRI is the first option after initial echocardiography for further assessment of cardiomyopathies, myocarditis and coronary anomalies, which are major causes of sudden cardiac death in young athletes. For athletes over 35 years of age the most common cause of sudden cardiac death is coronary artery disease, whereby cardiovascular screening requires further diagnostic modalities and may include multidetector CT.